Compulsion Symptoms among Health Care Providers during the Pandemic of Corona at Baghdad Teaching Hospital - Shatha Salah Jaseem; Mohammed Baqer Al-Jubouri (Iraqi National Journal of Nursing Specialties, 2022)
Objectives: The present study aimed to assess the compulsion among health care providers during the pandemic of COVID-19. Methodology: a descriptive design was used in the present study. This study was conducted from October 10th, 2020 through May 20th, 2021. The study was conducted on a probability (convenient) sample of 248 physicians and nurses who work at Baghdad Teaching hospital in Baghdad city. The instrument was used in this study is the COVID Stress Scale-Arabic version (CSS). Results: The result of this study showed that 42 % of HCPs had moderate symptoms and 36% of them had mild compulsive symptoms, and only 13% have severe compulsive symptoms according to the score of COVID stress scale. Conclusions: 78.6 % of the participants had mild to moderate compulsive and 13.7% had sever compulsion. Recommendations: All HCPs must get regular and thorough training on how to deal with the pandemic, and there is a need for more researches on how infectious disease epidemics affect the mental health of HCPs.